Atopic dermatitis in the elderly: a review of clinical and pathophysiological hallmarks. (28th July 2019) - Williamson, S.; Merritt, J.; De Benedetto, A.
Summary: Background: Atopic dermatitis (AD) is a multifactorial and complex disease, characterized by an impaired skin barrier function and abnormal immune response. Many elderly patients present with pruritus and xerosis to dermatology, allergy and primary care clinics, and there is a lack of information available to clinicians regarding the proper diagnosis and management of these patients. Although the elderly are described as having a distinct presentation of AD and important comorbidities, most investigations and clinical care guidelines pertaining to AD do not include patients aged 60 years and older as a separate group from younger adults. Objectives: To summarize current information on pathophysiology, diagnosis and management of AD in the elderly population and identify areas of insufficient information to be explored in future investigations. Methods: We carried out a systematic review of published literature, which assessed changes in the skin barrier and immune function with ageing and current information available for physicians to use in the diagnosis and treatment of AD in elderly patients. Results: Many age‐related changes overlap with key hallmarks observed in AD, most notably a decline in skin barrier function, dysregulation of the innate immune system, and skewing of adaptive immunity to a type‐2 T helper cell response, in addition to increased Staphylococcus aureus infection. Conclusions: While general physiological alterations with ageing overlap with key features of AD, a research gap exists regarding specific ageing‐related changes in AD disease development. More knowledge about AD in the elderly is needed to establish firm diagnostic and treatment methodologies. What's already known about this topic? Atopic dermatitis (AD) is a common inflammatory skin disease that causes significant burden worldwide. Recently, elderly patients have been considered a subgroup of patients with distinct AD manifestation. Limited studies have characterized the clinical presentation and role of IgE‐mediated allergy in elderly patients with AD. What does this study add? This review offers a summary of age‐related skin and immune alterations that correspond to pathogenic changes noted in patients with AD. The role of itch, environmental factors and skin microbiota in AD disease presentation in ageing patients is explored. Abstract : Plain language summary available online Linked Comment: Szegedi. Br J Dermatol 2020; 182 :9–10 .